A Governance-First and Systems-Theoretic Framework for Scalable Enterprise Cloud Integration Architecture - Chakra Dhari Gadige (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Enterprise cloud integration has traditionally been approached as a collection of discrete interfaces and data pipelines connecting heterogeneous systems. Such linear integration models are effective at a limited scale, but they might fail when it comes to nonlinear behavior, feedback effects and governance risks, which grow with the growth of enterprise complexity. This article explains enterprise cloud integration architecture as a complex adaptive system made of interacting and evolving subsystems, state dependencies, and governance boundaries. The article proposes a governance-first systems-theoretic framework that focuses on formal separation of control and data planes, embedded compliance and security mechanisms, predictive scalability modeling, and observability-driven feedback mechanisms. By treating governance as a stabilizing architectural invariant rather than a reactive constraint, the framework enables sustainable scalability, resilience, and long-term adaptability in enterprise cloud ecosystems. DOI: https://doi.org/10.17762/ijisae.v14i1s.8175